Does laboratory cue reactivity correlate with real-world craving and smoking responses to cues?. (1st October 2015) - Shiffman, Saul; Li, Xiaoxue; Dunbar, Michael S.; Tindle, Hilary A.; Scholl, Sarah M.; Ferguson, Stuart G.
Highlights: Smokers' responses to cues were assessed in a cue reactivity (CR) lab and via EMA. Analyses correlated craving and smoking in response to diverse cues in CR and EMA. CR cue responses were not correlated with real-world EMA responses to similar cues. Abstract: Background: Laboratory cue reactivity (CR) assessments are used to assess smokers' responses to cues. Likewise, EMA recording is used to characterize real-world response to cues. Understanding the relationship between CR and EMA responses addresses the ecological validity of CR. Methods: In 190 daily smokers not currently quitting, craving and smoking responses to cues were assessed in laboratory CR and by real-world EMA recording. Separate CR sessions involved 5 smoking-relevant cues (smoking, alcohol, negative affect, positive affect, smoking prohibitions), and a neutral cue. Subjects used EMA to monitor smoking situations for 3 weeks, completing parallel situational assessments (presence of others smoking, alcohol consumption, negative affect, positive affect, and smoking prohibitions, plus current craving) in smoking and non-smoking occasions (averaging 70 and 60 occasions each). Analyses correlated CR craving and smoking cue responses with EMA craving and smoking correlations with similar cues. Results: Although some cues did not show main effects on average craving or smoking, a wide range of individual differences in response to cues was apparent in both CR and EMA data, providing the necessary context to assess their relationship. Laboratory CR measures of cue response were not correlated with real-world cue responses assessed by EMA. The average correlation was 0.03; none exceeded 0.32. One of 40 correlations examined was significantly greater than 0. Conclusions: Laboratory CR measures do not correlate with EMA-assessed craving or smoking in response to cues, suggesting that CR measures are not accurate predictors of how smokers react to relevant stimuli in the real world.